1993
DOI: 10.3758/bf03213395
|View full text |Cite
|
Sign up to set email alerts
|

One bottle too many? Method of testing determines the detection of overshadowing and retention of taste aversions

Abstract: A two-bottle testing method generally is regarded as a more sensitive measure of taste aversions than a one-bottle test. The current research compared the sensitivity of one-bottle and twobottle tests in the detection of taste aversions. Specifically, the experiments were designed to detect both overshadowing (single-vs. compound-element conditioning) and retention interval (5 days vs. 1 day) effects. The groups tested with the one-bottle method evidenced both significant overshadowing and stronger aversions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 16 publications
4
46
1
Order By: Relevance
“…These differences are direct replications of the retention interval effect that has been reported previously (e.g., Batsell & M. R. Best, 1992aBest, , 1992bBest, , 1993Biederman et al, 1974). Second, at the 5-day interval, a single US preexposure did not alter the strength of the aversion compared with that of a nonpreexposed control.…”
Section: Groupssupporting
confidence: 66%
See 1 more Smart Citation
“…These differences are direct replications of the retention interval effect that has been reported previously (e.g., Batsell & M. R. Best, 1992aBest, , 1992bBest, , 1993Biederman et al, 1974). Second, at the 5-day interval, a single US preexposure did not alter the strength of the aversion compared with that of a nonpreexposed control.…”
Section: Groupssupporting
confidence: 66%
“…A one-bottle test was used because previous research has shown that it is more effective than a two-bottle method in detecting retention interval differences (Batsell & M. R. Best, 1993). Testing occurred over 2 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Testing of aversions to the AL solution was conducted for 20 min daily on Days 5-9. A single-bottle test was chosen because previous work has shown this testing method to be more sensitive in detecting aversions of differential strength (Batsell & Best, 1993). Access for 20 min to supplemental water was provided in the afternoons (4 h after any experimental procedures) on all days.…”
Section: Methodsmentioning
confidence: 99%
“…It may be that any alternative detection procedure would have provided evidence for a conditioned salt aversion. For example, in many situations a two-bottle preference test has been shown to be a more sensitive procedure for indexing taste aversions than a one-bottle test (e.g., Dragoin, McCleary, & McCleary, 1971;Grote & Brown, 1971; but see Batsell & Best, 1993). If so, then a two-bottle preference test between the water and the salt solution used here might have revealed a decrease in preference for the salt solution in rats given salt-morphine pairings relative to controls (i.e., salt aversion).…”
Section: Methodsmentioning
confidence: 99%